1982
DOI: 10.1007/bf02372456
|View full text |Cite
|
Sign up to set email alerts
|

Available phosphate content of an alluvial soil as influenced by inoculation of some isolated phosphate-solubilizing micro-organisms

Abstract: Summary Among several phosphate-solibilizing micro-organisms isolated from an alluvial soil (Fluvaquent) in sucrose-Ca3(PO,~) 2 agar plates, two fungal strains, ACF2 (Aspergillus eandidus) and ACF Z (A. fumigatus) two bacterial strains, ACB s (Baeillusfirmus B-7650) and ACB~ (B. firmus B-7651) and one actinomycete strain, ACSo (Streptomyces sp.) were efficient solubilizers, solubilizing 297.0, 288.3, 49.0, 45.8 and 29.0 p.g of P as free PO4 -3, respectively, containing 15 mg insoluble P from Ca3(PO4) 2 in brot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
51
0
8

Year Published

1992
1992
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(70 citation statements)
references
References 6 publications
5
51
0
8
Order By: Relevance
“…This observation in consistent with earlier reports, which have shown that the very low Al phosphate solubilization by Burkholderia cepacia DA23 (Song et al, 2008). This may be probably due to the adaptive nature of the enzyme that is responsible for solubilizing Ca 3 (PO 4 ) 2 (Banik and Dey, 1982). However, a few reports have indicated the other soil microorganisms to solubilize hardly soluble Fe or Al phosphates (Barroso et al, 2006;Antoun, 2002).…”
Section: Assay Of Inorganic Phosphate Solubilizing Abilitiessupporting
confidence: 91%
“…This observation in consistent with earlier reports, which have shown that the very low Al phosphate solubilization by Burkholderia cepacia DA23 (Song et al, 2008). This may be probably due to the adaptive nature of the enzyme that is responsible for solubilizing Ca 3 (PO 4 ) 2 (Banik and Dey, 1982). However, a few reports have indicated the other soil microorganisms to solubilize hardly soluble Fe or Al phosphates (Barroso et al, 2006;Antoun, 2002).…”
Section: Assay Of Inorganic Phosphate Solubilizing Abilitiessupporting
confidence: 91%
“…Além disso, existem diferenças na capacidade e no potencial de solubilização dos microrganismos. Determinado microrganismo pode solubilizar apenas Ca-P, enquanto outros ainda solubilizam Al-P e Fe-P, devendo-se levar em consideração que os microrganismos podem solubilizar esses fosfatos em diferentes intensidades (Banik & Dey, 1982;Doyle et al, 1990).…”
Section: Introductionunclassified
“…Na avaliação do efeito de fontes de carbono, foram utilizados 21 isolados selecionados de acordo com suas características morfofisiológicas (Silva Filho, 1998) Nenhum isolado produziu halo no meio com fosfato de ferro, apenas cinco produziram-no na presença de fosfato de alumínio e, com exceção do isolado 148, todos solubilizaram fosfato de cálcio. A baixa incidência de microrganismos solubilizadores de fosfatos de cálcio que solubilizam fosfatos de alumínio ou de ferro também tem sido encontrada por outros autores (Banik & Dey, 1982;Toro et al, 1996). Em alguns casos, os isolados solubilizam somente fosfatos de cálcio (Louw & Webley, 1959;Duff et al, 1963;Wenzel et al, 1994).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Phosphate solubilization by PSB strain is associated with the release of low molecular weight organic acids, which causes their hydroxyl and carboxyl group to chelate the unwanted cations bound with phosphate converting it from insoluble form to soluble form [16][17][18]. The process is followed by the release of organic acids such as glycolic, oxalic, malonic and succinic acid into the surrounding media by the PGPR strains, most of which have been reported to have efficient phosphorus solubilizing ability [19]. In addition to this, PSB strains releases inorganic acids like sulphidric, carbonic and nitric acid, which further act as a chelating agent thus transferring P into soluble form for the easy utilization of crops [20 -23].…”
mentioning
confidence: 99%